KOMPARASI REKSADANA SAHAM KONVENSIONAL DENGAN REKSADANA SAHAM SYARIAH - Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to determine whether there is a difference between the performance of Islamic mutual funds and conventional mutual funds in bullish and bearish market trends. The analytical method used is the mean difference test uses the independent sample t-test method, through the SPSS program by comparing the Jensen and Treynor indices. The samples of this study were 15 conventional mutual funds and 15 sharia mutual funds based on the highest achieved NAV. in each period 2017 as a bullish trend period  and the 2020 period as a bearish trend period. Based on the Jensen index by Independent sample t-test in 2017 (bullish trend), there is a significant difference between the performance of conventional stock mutual funds and the performance of Islamic stock mutual funds and the performance of conventional stock mutual funds is better than Sharia, while in the 2020 (Bearish trend) there is no differene between performance of conventional equity mutual funds and performance of Islamic equity mutual funds. Based on the Treynor index by independent sample t-test in both bullish and bearish periods, there is no difference between the performance of conventional equity funds and the performance of Islamic equity funds